A Bibliometric Analysis of Cyber Resilience from 2000 to 2024 - Muslikhatin, Lilik; Rodon Pedrason; Yoedhi Swastanto; Rudi Laksmono (Brawijaya Journal of Social Science, 2025)
The issue of cyber resilience is a growing global concern, as it reflects a country's ability to prepare for, absorb, recover from, and adapt to cyber threats and attacks. Weak cyber resilience can intensify the rise of digital crimes, making nations more vulnerable to disruption. This study aims to explore and analyse the development of cyber resilience research from 2000 to 2024 through a bibliometric approach. Data was collected from three major academic databases, Scopus, OpenAlex, and Google Scholar which are using relevant keywords such as cyber resilience, cyber security, cybercrime, and cyber defence. VOSviewer software was utilized to create network visualizations that map the connections between authors, research topics, institutions, countries, and keywords. The findings reveal a significant increase in scholarly publications over the years, indicating a growing global interest in this domain. Key research areas such as Cyber-Physical Systems (CPS), cyber resilience strategies, and social technologies have shown notable development. Furthermore, the focus of research has gradually shifted from purely technical aspects to more interdisciplinary themes involving public policy, international relations, risk governance, and the social sciences. The COVID-19 pandemic served as a turning point, amplifying research on societal impacts, remote work vulnerabilities, and risk communication. This evolution emphasizes the need for a holistic and integrated research agenda. The study concludes that international cooperation among scholars and institutions is crucial to strengthen cyber resilience. Future research directions should emphasize multidisciplinary and multimodal approaches to navigate the increasingly complex and interconnected landscape of cyber resilience, particularly in emerging domains such as social media governance, digital democracy, and AI-driven security.